Morphological variations of gynostemium and floral biology of Thottea ponmudiana Sivar., an endemic species of the Western Ghats, India - Sayoojia, K S; Sreekala , A K; Shaiju , P N (Plant Science Today, 2024)
Thottea ponmudiana is an endemic species restricted to the Ponmudi hills, a part of Agasthyamala Biosphere Reserve, Western Ghats, India. The gynostemium morphology is quite interesting in T. ponmudiana as this is a partial fusion product of the male and female reproductive parts. The present study deals primarily with the micromorphological analysis of gynostemium, with particular emphasis on its appendages and lobes and the floral biology of T. ponmudiana. The morphological variations in the gynostemium are discussed from the evolutionary point of view.